2019
DOI: 10.1038/s41419-019-1479-3
|View full text |Cite
|
Sign up to set email alerts
|

Lnc SMAD5-AS1 as ceRNA inhibit proliferation of diffuse large B cell lymphoma via Wnt/β-catenin pathway by sponging miR-135b-5p to elevate expression of APC

Abstract: Diffuse large B cell lymphoma (DLBCL) is a common and fatal hematological malignancy. Long noncoding RNAs (lncRNAs) have emerged as crucial biomarkers and regulators in many cancers. Novel lncRNA biomarker in DLBCL needs to be investigated badly, as well as its function and molecular mechanism. To further explore, microarray analysis was performed to identify the differentially expressed lncRNAs in DLBCL tissues. To investigate the biological functions of SMAD5-AS1, we performed gain- and loss-of-function expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 45 publications
2
96
0
Order By: Relevance
“…Previous evidence has revealed that Raf-1 is a new direct target of miR-195, and the expression of Raf-1 is markedly decreased by miR-195 (34). Similarly, SMAD5-AS1 is reported to be a ceRNA of miR-135b-5p to upregulate APC expression in diffuse large B cell lymphoma (35). Subsequently, the findings of this study showed that SMAD5-AS1 upregulated SMAD5 via competitively binding to miR-195 in NPC.…”
Section: Discussionsupporting
confidence: 55%
“…Previous evidence has revealed that Raf-1 is a new direct target of miR-195, and the expression of Raf-1 is markedly decreased by miR-195 (34). Similarly, SMAD5-AS1 is reported to be a ceRNA of miR-135b-5p to upregulate APC expression in diffuse large B cell lymphoma (35). Subsequently, the findings of this study showed that SMAD5-AS1 upregulated SMAD5 via competitively binding to miR-195 in NPC.…”
Section: Discussionsupporting
confidence: 55%
“…n = three independent repeats, *P < .05 SMAD5-AS1 plays a tumour suppressive role in DLBCL by inhibiting cell proliferation in vitro and repressing tumour growth in vivo. 39 LncRNA PANDA leads to cell cycle arrest at G0/G1 phase in DLBCL cells. 40 Conversely, lncRNA MALAT-1 contributes to proliferation and cell cycle progression, and it represses apoptosis of DLBCL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that lncRNAs function as oncogenes or tumour suppressors in DLBCL. For instance, lncRNA SMAD5‐AS1 plays a tumour suppressive role in DLBCL by inhibiting cell proliferation in vitro and repressing tumour growth in vivo . LncRNA PANDA leads to cell cycle arrest at G0/G1 phase in DLBCL cells .…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous studies have revealed its important roles in cellular processes, such as X chromosome inactivation, splicing, imprinting, epigenetic control, and gene transcription regulation [1][2][3]. Moreover, some have shown that lncRNAs could function as a competing endogenous RNA (ceRNA) to sponge miRNAs, thereby preventing microRNAs from binding to their target genes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%